Relationship between Coaches' Leadership Style and Athletes' Performance in Kwara State Sports Council - Adebayo Babatunde Samson; Surajudeen Tosho Bakinde (The Sky, 2021)
Leadership in coaching is a critical component to enhance and sustain optimal sports performance and athletes’ satisfaction. This study investigated the influence of coaches' leadership styles on athletes’ performance in Kwara State Sports Council.  Descriptive survey design of correlational type was employed. The sample of the study comprised 150 athletes selected using simple random and proportionate sampling techniques. Standardized questionnaire (Leadership Scale for Sports) was the instrument for data collection. Descriptive statistics and Pearson Product Moment Correlation (PPMC) statistic was used to analyze the data. The findings of the study revealed that training behavior, autocratic behavior, democratic behavior, social support, and rewarding behavior of the coach have significant influence on athletes' performance in the study area. Based on the findings, it was recommended that the management of Kwara State Sports Council should establish a mechanism for positive feedback and social support to foster good leadership behaviour to assist in enhancing athletes' performance.